Evaluasi Efektivitas Soil Bioengineering Berbasis Vegetasi Pinus terhadap Pengendalian Sedimen di Lereng DAS Jene’berang - Mahmuddin; Ali, Muhammad Yunus; Asdin Agus Salim, Muh. (Jurnal Karajata Engineering, 2026)
The Jene'berang River Basin is one of the main river basins in South Sulawesi Province, which has a high level of sedimentation and landslide vulnerability due to a combination of factors, including steep topography, unstable soil types, high rainfall, and changes in land use. This study aims to analyze the effectiveness of applying pine vegetation-based bioengineering technology in sediment control in the Jene'berang-Jenelata watershed. The research method was conducted from January to June 2025 through field observations, spatial analysis using Geographic Information Systems and measurements of sediment landslide volumes at several variations of pine vegetation planting distances. The parameters analyzed included soil classification, land activity, slope gradient, rainfall, and sediment landslide volume. The results showed that the application of bioengineering had an effect on sediment control, with variations in vegetation planting distance affecting the volume of landslides that occurred. Wider planting distances showed higher sediment retention efficiency compared to very dense planting distances. The appropriate and integrated application of bioengineering technology with the physical characteristics of the watershed is expected to be a sustainable solution for sediment control and landslide mitigation in the Jene'berang watershed.